Utilization of Two Distinct Modes of Replication by a Hybrid Plasmid Constructed In Vitro from Separate Replicons - Timmis, Kenneth (1974)
A hybrid plasmid, pSC134, that codes for two distinct sets of replication functions has been constructed in vitro by ligation of EcoRI endonuclease-cleaved pSC101 and Col E1 plasmid replicons, and has been introduced into Escherichia coli by transformation. The replication properties of the pSC134 plasmid in DNA polymerase I-defective mutants or in the presence of chloramphenicol indicate that this hybrid plasmid can utilize the functionally distinct modes of replication specified by both of its parent replicons.